Cultural dynamics and production activities in ancient western Mexico : papers from a symposium held in the Center for Archaeological Research, El Colegio de Michoacán 18-19 September 2014 - Williams, Eduardo; Maldonado, Blanca (Archaeopress, 2016)
This title presents a collection of papers from the Symposium on Cultural Dynamics and Production Activities in Ancient Western Mexico, held at the Center for Archaeological Research of the Colegio de Michoacán on September 18-19, 2014. While these thought-provoking essays on key topics in Western Mexican archaeology will spark debate among scholars interested in this cultural area, they will also be of interest to students of ancient Mesoamerica as a whole. The time is ripe for insightful discussions and new syntheses of archaeological research in Western Mesoamerica, and this volume represents, undoubtedly, a valuable contribution to this urgent task.